Prognostic Significance of ABPM in Comparison to Clinical Blood Pressure Monitoring and their Association with Various Risk Factors Involved in CKD Predisposition in North Indian Patients - seema singh; syed tahseen raza; nitin ranjan gupta; rahul singh (Journal of Clinical and Diagnostic Research, 2021)
Introduction: Ambulatory Blood Pressure Monitoring (ABPM) has been found to be a more reliable method for diagnosing Hypertension (HTN) and stratifying cardiovascular risk than Continuous Blood Pressure (CBP) monitoring. Aim: To evaluate prognostic significance of ABPM in comparison to clinical Blood Pressure (BP) Monitoring and their association with various risk factors involved in Chronic Kidney Disease (CKD) patients. Materials and Methods: This was a prospective study done in Era’s Lucknow Medical College and Hospital, Lucknow, Uttar Pradesh, India. Routine laboratory tests were conducted for all patients. Casual Blood Pressure (BP) was obtained by a trained staff through a digital BP monitor (CITIZEN-CH-432) and Meditech ABPM-05 device was used for ABPM. Pearson's correlation method was used to analyse the relationship between the two continuous variables. Results: Present study included 400 patients of which 225 (56.25%) were male subjects, and mean age was 62 (Range21-76) years. Of the study population, 90 (22.5%) were CKD G1-2, 79 (19.75%) were CKD G3a, 96 (24%) were CKD G3b, and 135 (33.75%) were CKD G4. Among all the patients included in the study, the most common was normal BP (33.75%), sustained HTN (26.25%), White Coat Hypertension (WCH) (6.5%), and masked HTN (33.5%). When multiple logistic regression analyses were done, estimated Glomerular Filtration Rate (eGFR), and BP data, night-time Systolic Blood Pressure (SBP) (OR, 1.043; 95% CI, 1.025-1.067; p<0.001), and night-time Diastolic Blood Pressure (DBP) was found (OR, 1.050; 95% CI, 1.013-1.075) to have an independent association with non/reverse-dippers. Conclusion: The ABPM has more prognostic significance when compared to office BP measurements in all kind of normotensive, hypertensive and CKD patients at all stages. ABPM measurements are often abnormal in CKD, with CKD patients frequently showing an altered circadian rhythm with an increased rate of non dipping and reverse dipping